THE USE OF (MEMRISE) APPLICATION TO IMPROVE ENGLISH SPEAKING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Bela Ayu Permatasari; Annisa Fauziah; Afnal Lazuardi; Naf’anTarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
Speaking is a key skill in English learning, yet many EFL learners still struggle with vocabulary, pronunciation, and confidence. With the rise of MALL, Memrise has become a popular tool that offers spaced repetition, native-speaker audio, and gamified features that may support speaking development. This study aims to conduct a Systematic Literature Review (SLR) to examine how Memrise helps improve English-speaking skills. The main research problem is: How effective is Memrise in enhancing learners’ speaking skills? A secondary problem is: Which speaking aspects—vocabulary, pronunciation, fluency, or confidence—show the most improvement? Using the PRISMA 2020 framework, ten empirical studies were analyzed. The findings show that Memrise supports speaking development mainly through better vocabulary retention, improved pronunciation, and increased motivation, although real communicative practice is still needed for full fluency